(Invited) Graphene for Biosensor Applications. (18th August 2016) - Matsumoto, Kazuhiko
Abstract : As graphene has the two-dimensional electron gas with ultra high mobility on its surface, it is the optimal material for sensor application with high-sensitivity. In this study, we have succeeded in selective detection of the bird and human influenza virus using the sugar chain modified graphene FET for the first time.